2018
DOI: 10.1177/0956797618779590
|View full text |Cite
|
Sign up to set email alerts
|

Extraordinary Altruists Exhibit Enhanced Self–Other Overlap in Neural Responses to Distress

Abstract: Shared neural representations during experienced and observed distress are hypothesized to reflect empathic neural simulation, which may support altruism. But the correspondence between real-world altruism and shared neural representations has not been directly tested, and empathy's role in promoting altruism toward strangers has been questioned. Here, we show that individuals who have performed costly altruism (donating a kidney to a stranger; n = 25) exhibit greater self-other overlap than matched control pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 42 publications
4
48
0
Order By: Relevance
“…The finding that negative empathic affect was positively associated with donation behavior within each condition in almost all cases is consistent with heightened affective resonance with distress in extraordinary altruists observed in prior work (Marsh et al, 2014;Brethel-Haurwitz et al, 2017;Brethel-Haurwitz et al, 2018), and also with theories of altruism emphasizing the role for concern in promoting prosociality (e.g., Nichols, 2001;Batson, 1991). Though participants were not instructed to increase positive emotions, this was a byproduct of hopeful reappraisal.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…The finding that negative empathic affect was positively associated with donation behavior within each condition in almost all cases is consistent with heightened affective resonance with distress in extraordinary altruists observed in prior work (Marsh et al, 2014;Brethel-Haurwitz et al, 2017;Brethel-Haurwitz et al, 2018), and also with theories of altruism emphasizing the role for concern in promoting prosociality (e.g., Nichols, 2001;Batson, 1991). Though participants were not instructed to increase positive emotions, this was a byproduct of hopeful reappraisal.…”
Section: Discussionsupporting
confidence: 71%
“…All participants completed the same battery of behavioral tasks and questionnaires. Twenty-nine altruists and 26 controls in this study also completed a neuroimaging component prior to the procedures of this study, which is partially reported elsewhere (Brethel-Haurwitz et al, 2018). Electrodermal activity data were missing from 6 controls and 3 altruists due to equipment malfunction or experimenter error, yielding a subsample of 22 controls and 27 altruists.…”
Section: Study 2 Methodsmentioning
confidence: 99%
See 3 more Smart Citations